Risk Factor Analysis Of The Severity Chronic Kidney Failure Undergoing Hemodialysis At State Hospital - Galih Persadha; Rosihan Adhani; Syamsul Arifin; Husaini Husaini; Meitria Syahadatina Noor (Healthy-Mu Journal, 2021)
Chronic kidney disease (CKD) is ranked 27th cause of death in the world in 1990 and increased 18th in 2010. The results of Riskesdas in 2013 showed the prevalence of CKD in Indonesia by 0.2% or 2 per 1000 population. A long history of hypertension and kidney stones can cause a decrease in kidney function, patients with chronic renal failure who are still working have a level of fatigue that can trigger stress. Working conditions outdoors in hot temperatures can result in dehydration. The severity of patients with chronic kidney failure can be influenced by hypertension, kidney stones and work. Objective: To analyze risk factors for the severity of chronic kidney failure that undergo hemodialysis at Ulin Regional Hospital in South Kalimantan. Method: An observational analytic study with a cross sectional study design. A sample of 65 patients using simple random sampling. The research instrument used patient medical record data. Data analysis with descriptive and statistical namely chi square and multiple logistic regression. Results: Patients who also suffered from hypertension had a greater risk for end-stage CKD (p = 0.010). Patients who also suffered from kidney stones had a greater risk for end-stage CKD (p = 0.034). Kidney failure patients who are still working have a risk of CRF (p = 0.011). Analysis using multiple logistic regression showed hypertension variables (p = 0.010; Exp.B = 7.236), kidney stones (p = 0.034; Exp.B = 5.221), and occupation (p = 0.011; Exp.B = 5.424) with a level of confidence 95%. Conclusion: There is a relationship between hypertension, kidney stones, and occupation with the severity of chronic kidney failure, with the most dominant variable hypertension among the three variables.